Geometrical frustration and static correlations in hard-sphere glass formers - Benoit Charbonneau; Patrick Charbonneau; Gilles Tarjus (Journal of Chemical Physics, 2013)
We analytically and numerically characterize the structure of hard-sphere fluids in order to review various geometrical frustration scenarios of the glass transition. We find generalized polytetrahedral order to be correlated with increasing fluid packing fraction, but to become increasingly irrelevant with increasing dimension. We also find the growth in structural correlations to be modest in the dynamical regime accessible to computer simulations.